2021
DOI: 10.5688/ajpe8073
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Escape Room to Increase Pharmacy Preceptor Knowledge of the Pharmacists’ Patient Care Process

Abstract: Objective. To design and assess the use of an escape room for pharmacy preceptor development.Methods. An escape room was created for preceptors focused on the Pharmacists' Patient Care Process (PPCP), preceptor resources and the School of Pharmacy's mission and vision. Teams were to solve digital and practical puzzles to escape a pharmacy. The fastest team to correctly solve all the puzzles was considered to have escaped the pharmacy. Escape room puzzles included digital locks, cipher wheels, a rebus puzzle, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Serious games such as escape rooms are an entertaining and engaging method of delivering learning materials and have become a popular learning tool in medical (Backhouse & Malik, 2019 ; Guckian et al, 2020 ; Wiemker, 2015 ) and pharmacy education (Badr, 2022 ; Cain, 2019 ; Caldas et al, 2019 ; Clauson et al, 2019 ; Cole & Ruble, 2021 ; Richter & Frenzel, 2021 ; Eukel et al, 2017 ; Gordon et al, 2019 ; Kavanaugh et al, 2020 ) due to the generational shift in the current learner population and the societal impact of gamification (Guckian et al, 2020 b). A good escape room activity allows for achievable goals, autonomy for freedom of choice for learners and incorporates teamwork (Guckian et al, 2020 a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious games such as escape rooms are an entertaining and engaging method of delivering learning materials and have become a popular learning tool in medical (Backhouse & Malik, 2019 ; Guckian et al, 2020 ; Wiemker, 2015 ) and pharmacy education (Badr, 2022 ; Cain, 2019 ; Caldas et al, 2019 ; Clauson et al, 2019 ; Cole & Ruble, 2021 ; Richter & Frenzel, 2021 ; Eukel et al, 2017 ; Gordon et al, 2019 ; Kavanaugh et al, 2020 ) due to the generational shift in the current learner population and the societal impact of gamification (Guckian et al, 2020 b). A good escape room activity allows for achievable goals, autonomy for freedom of choice for learners and incorporates teamwork (Guckian et al, 2020 a).…”
Section: Discussionmentioning
confidence: 99%
“…Students who did not have any part time work experience in healthcare sectors demonstrated significant improvement in their knowledge on the topic, similar to their peers who have previous work experience, corroborating the fidelity of the gamebased learning activity in augmenting students' knowledge gain. Serious games such as escape rooms are an entertaining and engaging method of delivering learning materials and have become a popular learning tool in medical (Backhouse & Malik, 2019;Wiemker, 2015) and pharmacy education (Badr, 2022;Cain, 2019;Caldas et al, 2019;Clauson et al, 2019;Cole & Ruble, 2021;Richter & Frenzel, 2021;Eukel et al, 2017;Gordon et al, 2019;Kavanaugh et al, 2020) due to the generational shift in the current learner population and the societal impact of gamification (Guckian et al, 2020b). A good escape room activity allows for achievable goals, autonomy for freedom of choice for learners and incorporates teamwork (Guckian et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…7 Literature has suggested that educational escape rooms can increase knowledge, improve clinical skills, promote critical thinking, allow for the application of concepts and encourage teamwork. [7][8][9][10] Benefits of virtual escape rooms include lower costs and minimal preparation for coordinators after initial development with the ability to use for multiple years. 9 The curricular meshing of pharmaceutical sciences and clinical practice is an important strategy in healthcare education.…”
Section: Introductionmentioning
confidence: 99%
“…Many published papers described the efficacy of such a model, as well as an increase in knowledge and improvement in clinical skills. Moreover, students have perceived pharmacy educational escape rooms to positively impact their engagement, clinical thinking, problem-solving, teamwork and application of learned in-class concepts [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], skills that are all needed in pharmacy real-world and day-to-day tasks.…”
Section: Introductionmentioning
confidence: 99%